Strategi Pengembangan Biodiesel Untuk Sektor Transportasi Darat yang Berkelanjutan di Sulawesi Selatan - Rodrick Kristianturi; Muhammad Yamin Jinca; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Nowadays, the world is facing the challenge of energy uncertainty. Energy utilization is still dominated by fossil fuel whereas these fuel will run out. The use of fossil fuels also contributes to build up the greenhouse gas emissions in the atmosphere and continues to burden the government through the cost of fuel importing and subsidies. South Sulawesi with relatively large fuel consumption still uses fossil fuel especially at transportation sector. The use of fossil fuel is not an effective decision considering there are still many renewable energy which have not been utilized properly such as biodiesel. The aim of this research is to explain development strategy of biodiesel application as a renewable alternative fuel for the sustainable of land transportation sector at Sulawesi Selatan. This research was conducted from July 2019 to February 2020 (8 months).The method of this research are quantitative and qualitative descriptive. Data were obtained through agency documents, interview, and literature review. The results showed development strategy refers to the Strength-Threat strategy which is conglomerate diversification strategy by increasing the feedstock production from non existing land to fulfill the needs of biodiesel.